Uncovering the mysteries of human gamma delta T cells: from origins to novel therapeutics - Biały, Sylwia; Bogunia-Kubik, Katarzyna (Frontiers in Immunology, 2025)
Gamma delta (γδ) T cells represent a unique and distinct population of lymphocytes that bridge the innate and adaptive immune responses. This functional duality positions them as one of the pivotal elements in the evolution and development of the human body’s defense mechanisms. This review aims to provide a comprehensive and in-depth overview of γδ T cells, covering their origins, development, classification, and functional roles in immunology. Special attention is given to their involvement in the pathogenesis of autoimmune and cancer-related diseases—areas that remain subjects of intensive research with many unanswered questions. Additionally, this article explores the therapeutic potential of γδ T cells, which hold promise as a novel approach to treating various difficult-to-manage diseases. The review also presents an analysis of the latest clinical studies utilizing γδ T cells, emphasizing their emerging role in modern medicine. The ultimate goal of this work is to offer a holistic perspective on the current state of research on γδ T cells and their prospective applications in immunotherapy and cancer treatment, highlighting their potential to become a groundbreaking tool in future medical interventions.